Company size on corporate social responsibility with the board of commissioners as mediation - Dwi Dewianawati; Agus Sunaryo; Buyung Cahya Perdana; Erry Setiawan (Institute of Computer Science (IOCS), 2022)
Information is a fundamental need for investors and potential investors for decision making. The existence of complete information, accurate and timely allows investors to be rational decision-making so that the results obtained as expected. Demands on companies to provide transparent information, the organization accountable and good corporate governance is increasingly forcing companies to provide information about social activities related to the organization's interaction with the physical environment and social environment, which is made in company annual reports or social reports separately. This study aims to examine some factors that affect the disclosure of corporate social responsibility. This study tried to develop a board of commissioners as the intervening variable of firm size on the disclosure of corporate social responsibility. The sample in this study was determined by sampling purposive. The population was 219 company listed on the Indonesia stock exchange. Data were analyzed using Path Analysis with SPSS. The results indicate that company size does not influence directly on the disclosure of corporate social responsibility, and commissars council cannot serve as an intervening variable in the influence of company size on disclosure of corporate social responsibility.